3D printing: A new pacesetter of industry 4.0 set to reduce the pollution of logistics cost - Degeras, D Karunanithy; Beleya, Prashanth; Selvaraju, Mohan (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores the evolution of printing created by the revolution of industry 4.0 in which 3D printing technology emerges as one of the trendsetter’s for the purpose of reducing logistics cost. Despite of the existence of technology during the third industrial revolution, 3D printing only emerged into extensive manufacturing digitalization in the fourth industrialization. Manufacturing and the logistics activities have constantly improvised through innovative measures to enhance processes to become more lean and agile. However, conventional manufacturing is less flexible, creates excessive wastages, can only achieve economies of scale when producing large quantity of products and longer time is taken to produce a new product. Breakthroughs in information technology, mobile communications and robotics have led to the growing use of digital technologies in factories around the world. This transformation has come to be known as Industry 4.0 or the Fourth industrial revolution. As such, 3D printing being part of the 4.0 revolution holds the ability to reduce costs that surfaces in logistics activities which could also improve manufacturing cost ultimately